Quantitative evaluation of unrelated diversification of enterprise activities - Ginevičius, Romualdas (Journal of Civil Engineering and Management, 2009)
Diversification of activities is one of the main strategies of an enterprise. This is a complicated and controversial process. Some consider it to be a perspective approach, while others think that it is too risky and, therefore, unreliable. To solve this problem, diversification of enterprise activities should be measured. A survey of the methods of diversification measurement shows that they are not accurate and do not reflect the real situation. With the increase of diversification of enterprise activities, two parameters, the number of divisions and the relationship between their activities, vary. The indicator of diversification should assess and integrate both parameters. In this process, the effect of each of the above parameters on the organisational structure, determining the outcome of diversification, should be examined. In this environment, the variation in the number of enterprise activities (or their directions) is more important because the establishment of new divisions depends on it. The variation in the relationships between the particular activities does not necessarily lead to the emergence of a new division. The calculations based on the data obtained from Lithuanian construction enterprises show that the indicator of enterprise diversificiation offered in the present paper satisfies all the considered requirements, while the calculations of its values for actual enterprises demonstrate that it may be successfully used in practice.Įmonių veiklos nesusijusios diversifikacijos kiekybinis įvertinimasSantrauka. Viena iš pagrindinių įmonių plėtros strategijų – jų veiklos diversifikacija. Šis fenomenas pasižymi dideliu kompleksiškumu, todėl yra gana prieštaringas. Vienais atvejais manoma, kad tai perspektyvus būdas, kitais – kad diversifikacija yra per daug rizikinga, todėl vargu ar prasminga. Norint atsakyti į šiuos klausimus, veiklos diversifikaciją reikia išmatuoti. Matavimo būdų apžvalga rodo, kad jie yra netikslūs ir neatspindi realios padėties. Stiprėjant įmonės veiklos diversifikacijai, kinta du įmonės parametrai – padalinių skaičius ir jų atliekamų darbų santykis. Diversifikacijos rodiklis turi abu šiuos parametrus tinkamai įvertinti ir sujungti. Tai atliekant reikia atsižvelgti į kiekvieno iš šių parametrų įtaką organizacinei įmonės struktūrai, svarbiausiam įmonės veiklos diversifikacijai padariniui. Svarbesnis yra įmonės veiklos krypčių skaičiaus kitimas, nes nuo jo priklauso naujų padalinių atsiradimas. Verslo variacija dar ne visada gali būti naujo padalinio atsiradimo priežastis. Pateikiamas įmonių veiklos diversifikacijos rodiklis atitinka visus šiuos reikalavimus. Jo reikšmių skaičiavimas realioms įmonėms parodė, kad jis gali būti taikomas praktiškai.Reikšminiai žodžiai: diversifikacija, diversifikacijos matavimas.First Published Online: 14 Oct 2010